Orthopaedic basic science foundations of clinical practice - Aaron, Roy K. (American Academy of Orthopaedic Surgeons, 2021)
"This edition represents the scientific basis of orthopaedic surgery as of 2020. It is intended to inform clinical decision making by providing the basic sciences in a clinically relevant context. The production of the fifth edition of Orthopaedic Basic Science was a substantial undertaking contributed to by each of the authors. The author list is comprised of senior scientists and clinicians, and rising stars, a healthy mixture that reflects well on both sustained personal commitments and expectations for the future. Reflecting the growth in orthopaedic scientific information, all the previously included chapters have been revised and many new chapters have been added. Molecular biology has been refocused to emphasize the role of epigenetics. Biomaterials, repair, and tissue engineering are also emphasized. The significance of articular crosstalk is presented together with new chapters on joint biology and osteoarthritis. Consideration of gender differences in preclinical and clinical studies recognizes the spectrum of biological responses and the presentation of metabolic bone diseases acknowledges the importance of secondary fracture prevention. A completely redone section on the generation of clinical information recognizes advances in methodology, the assessment of large databases and the growth of registries, and best-practice guidelines"--